ՀՀ-ում հասարակական կազմակերպությունների գործունեության առանձնահատկությունների մասին - Ստեփանյան Լիլիթ (YSU Journal of International Affairs, 2015)
The democratic political systems of the modern world is closely linked with civil society and legal system of the state. After the collapse of the Soviet Union, the former Soviet states were in an entirely new social, political, post-Soviet reality. Naturally, in each of them, including Armenia, together with the institutions of the political system, some institutions of the social system were formed and developed. Ideas about the political society of the third sector have been put forward; the laws governing this area have been developed. In connection with both political and non-political factors existing in Armenia nowadays social organizations present a number of structural and functional features that have positive and sometimes negative impact on the development and formation of the civil society of Armenia.